'Everyone is an individual': providing individualized treatment in oncology. (August 2015) - Thompson, Michael A
Michael A Thompson* speaks to Stella Bennett, Commissioning Editor: Michael A Thompson, MD, PhD is a hematologist/oncologist and researcher at Aurora Health Care (AHC) and the Aurora Research Institute (ARI). Dr Thompson is a native of Minnesota. He received his BS degree in Molecular Biology from the University of Wisconsin – Madison, his MD from Mayo Medical School and PhD in Molecular Pharmacology and Experimental Therapeutics from the Mayo Graduate School. He completed his Internal Medicine Residency at the Mayo Clinic College of Medicine. He obtained his Hematology/Oncology Fellowship at the University of Texas MD Anderson Cancer Center. Dr Thompson received the American Society of Clinical Oncology (ASCO) Young Investigator Award in 2006 and the American Society of Hematology Clinical Research Training Institute (ASH CRTI). After fellowship, he moved back to the Midwest, where he served as the Medical Director of Cancer Research at ProHealth Care Regional Cancer Center, as well as the local site Clinical Trials Lead Investigator of the NCI Community Cancer Centers Program (NCCCP) and national Co-Chair of the NCCCP Clinical Trials Portfolio/Accrual Log Working Group. He also was on the NCCCP Early Phase Working Group which focused on bringing new drugs to the community setting. In 2013 he joined AHC as the Medical Director of the Early Phase Cancer Research Program. Dr Thompson was a recipient of a Vince Lombardi Cancer Foundation (VLCF) funded Aurora Cancer Care Research Award (ACCRA) 'The Immune Response Following Vaccination in Multiple Myeloma Patients' which is an ongoing Aurora-based research study. In 2014, AHC received the NCI Community Oncology Research Program (NCORP) grant. Dr Thompson is the co-primary investigator. Dr Thompson has studied and published in the area of hematologic malignancies – myeloma, lymphoma, leukemia and other cancers. He is on the ECOG Myeloma Core Committee and the NCI Myeloma Steering Committee. He has a strong interest in clinical research in hematologic cancers as well as in new drug development in a variety of cancer types. He is currently on the ASCO Cancer Research Committee, ASCO Community Research Forum, and on various research subcommittees. He is active in social media (Twitter: @mtmdphd) with national presentations on the topic of the use of social media in oncology.